AB0892 NT-PROBNP in ankylosing spondylitis patients undergoing TNF blockage therapy: Correlation with inflammatory status independent of cardiovascular disease. (23rd January 2014) - Moraes, J.C.; Ribeiro, A.C.D.M.; Saad, C.G.S.; Lianza, A.C.; Silva, C.A.; Bonfa, E.
Abstract : Background: Inflammation may influence levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) 1-3 discrimination of this confounding variable is of particular interest in rheumatic diseases. 4 Objectives: We evaluated NT-proBNP levels in ankylosing spondylitis (AS) patients without systolic myocardial dysfunction pre- and post-TNF blocker initiation to determine the possible association between NT-proBNP levels and inflammatory parameters. Methods: Forty-five consecutive AS patients without previous/current cardiovascular disease, who were eligible to receive anti-TNF therapy, were prospectively enrolled. All patients were treated with TNF blockers, and they were evaluated for clinical and laboratory parameters of disease activity, traditional cardiovascular risk factors, conventional and tissue Doppler imaging echocardiography, and circulating NT-proBNP levels at baseline (BL) and six months after (6M) treatment. Results: All patients had active disease at BL [ASDAS-CRP=3.58 (1.11); ASDAS-ESR=3.02 (1.12); BASDAI=5.1 (2.2); CRP=1.89 (0.80-4.19) mg/dL; and ESR=16 (8-32.5) mm/1st h]. At BL, NT-proBNP levels were 36 (20-72) pg/ml, and multiple linear regression analysis revealed that this peptide was independently correlated with age (r=0.458, p=0.002) and ESR (r=0.398, p=0.007). From BL to 6M, all parameters improved, and NT-proBNP levels were significantly reduced [24 (16-47) pg/mL, p=0.037]. Changes in NT-proBNP levels were significantly correlated with ESR changes from BL to 6M (r=0.39, p=0.008) (Figure 1). Cardiovascular risk factors and echocardiography remained unchanged. Conclusions: NT-proBNP levels should be interpreted with caution in active AS patients with no evidence of CV disease. The prospective reduction of NT-proBNP in parallel with ESRsuggests that this peptide level is, to some degree, modifiable by inflammation status independent of cardiovascular disease. (ClinicalTrials.gov number, NCT01072058 ). References: Jensen J, Ma LP, Fu MLX, et al. Inflammation increases NT-proBNP and the NT-proBNP/BNP ratio. Clin Res Cardiol 2010;99:445-52. Meirovich YF, Veinot JP, de Bold MLK, et al. Relationship between natriuretic peptides and inflammation: proteomic evidence obtained during acute cellular cardiac allograft rejection in humans. J Heart Lung Transplant 2008;27:31-7. de Bold AJ. Cardiac natriuretic peptides gene expression and secretion in inflammation. J Investig Med 2009;57:29-32. Peters MJL, Welsh P, McInnes IB, et al. Tumour necrosis factor α blockade reduces circulating N-terminal pro-brain natriuretic peptide levels in patients with active rheumatoid arthritis: results from a prospective cohort study. Ann Rheum Dis 2010;69:1281-5. Disclosure of Interest: None Declared